Identitete in identifikacije - Medica, Karmen (Monitor ISH, 2009)
All culturally heterogeneous societies face identity crises, an indefinable multicultural reality, and political concepts seeking to identify the modern methods of managing cultural differences. The complex reasons for diversity and for insistence on specific identities include postcolonialism, globalisation, international migration flows, re-affirmation of ethnic minorities, native peoples' awareness-raising, as well as the expansion and development of the identity movements of women, homosexuals, the elderly, the disabled, and others. Modern identities tend to be derived and dialogical, liminal, transient, but they do open up new modes of identifying and understanding culture.
Keywords: družba; society; identiteta; kulturna identiteta; narodna identiteta